1994
DOI: 10.1177/112067219400400103
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 0.75% Bupivacaine with ph Adjustment and Hyaluronidase for Peribulbar Blockade: The Incidence of Prolonged Ptosis

Abstract: A prospective, double masked, randomised study was performed to compare the speed of onset of peribulbar anaesthesia using pH adjusted 0.75% bupivacaine, with and without the addition of hyaluronidase. No significant difference in speed of onset occurred due to the addition of hyaluronidase. There were 7 cases of post operative ptosis in the study group, including 1 case of orbital apex syndrome and 2 cases of transient 3rd nerve palsy. This incidence of post operative ptosis using pH adjusted 0.75% bupivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…9 There is conflicting evidence with regard to the influence of the composition of the solution injected on postoperative ptosis. Mather et al 23 found an increased incidence (19% vs. 2.7%) of transient postoperative ptosis with 0.75% bupivacaine with pH adjustment compared with 1:1 1% lidocaine and 0.5% bupivacaine. 23 The enhanced toxicity may be a result of the higher concentration of bupivacaine (0.75% vs. 0.5%) or the pH adjustment, which can increase the overall availability.…”
Section: Anesthetic Effectsmentioning
confidence: 96%
See 3 more Smart Citations
“…9 There is conflicting evidence with regard to the influence of the composition of the solution injected on postoperative ptosis. Mather et al 23 found an increased incidence (19% vs. 2.7%) of transient postoperative ptosis with 0.75% bupivacaine with pH adjustment compared with 1:1 1% lidocaine and 0.5% bupivacaine. 23 The enhanced toxicity may be a result of the higher concentration of bupivacaine (0.75% vs. 0.5%) or the pH adjustment, which can increase the overall availability.…”
Section: Anesthetic Effectsmentioning
confidence: 96%
“…Mather et al 23 found an increased incidence (19% vs. 2.7%) of transient postoperative ptosis with 0.75% bupivacaine with pH adjustment compared with 1:1 1% lidocaine and 0.5% bupivacaine. 23 The enhanced toxicity may be a result of the higher concentration of bupivacaine (0.75% vs. 0.5%) or the pH adjustment, which can increase the overall availability. 23 Epinephrine tends to potentiate the myotoxic effects.…”
Section: Anesthetic Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…[13][14][15] Although numerous clinical studies confirm the positive effect of the use of hyaluronidase, some studies suggest a lack of effect. [15][16][17] The objective of the present study was to test the efficacy and safety of hyaluronidase on the onset and adequacy of ocular akinesia and anesthesia after retrobulbar administration. …”
mentioning
confidence: 99%